Literatur-Zensur- und Gegenstrategien. Die Fälle Johannes R. Becher und Heinrich Mann in der Weimarer Republik - Haupt, Jürgen (Studia Germanica Posnaniensia, 2018)
Starting out from H. Mann's public statements about the trials against J.R. Becher's , Levisite“ and Arthur Schnitzler's , Reigen“ Haupt interprets H. Mann's journalistic campaign against literary censorship in the Weimar Republic as well es his role in the section , Literary Art“ of the Prussian Academy of Arts as being the heroic illusion of a courageous man striving to enlighten the public in the face of the emergence of fascism.